The Investment Paradox and Economic Sustainability in a Geopark: A Financial Feasibility Analysis of Tourism in Maros–Pangkep - Rahman, Abdu; Badollahi, Muh. Zainuddin; Nurjannah, Nurjannah; Wahyuni, Vini (SIGn Journal of Social Science, 2024)
Despite its prestigious status as a UNESCO Global Geopark, the economic sustainability of the Maros-Pangkep Geopark faces a crucial paradox between its international recognition and the reality of local-level investment. This study aims to dissect this paradox by comprehensively analyzing the tourism business architecture, the spectrum of financial feasibility, and the dynamics of investment and its impact on the local economy. The research adopts a mixed-methods approach using an explanatory sequential design, integrating descriptive statistical analysis and investment feasibility metrics (NPV, IRR, BCR) on primary and secondary data from 2019–2023, with a thematic analysis of in-depth interviews with key stakeholders. The findings reveal a dual economic structure. On one hand, a resilient, community-based business ecosystem is financially feasible at a subsistence level (IRR 12.5%; BCR 1.4), serving as the primary driver of the local economy through job creation. On the other hand, the region has failed to attract strategic, capital-intensive investment, reflected in the marginal contribution of tourism investment to the regional economy (<3%) due to perceived risks and structural challenges. It is concluded that the geopark’s current economic sustainability is sustained by an organic, bottom-up development model. However, it risks stagnation without proactive policies that bridge the vitality of the community economy with strategic, top-down capital flows.